Forty years of Segusino-Chipilo Twinning: integration and segmented assimilation of a veneti community in the Mexican highlands - Crivelli Minutti, Eduardo (Revista Española de Desarrollo y Cooperación, 2023)
The Chipilo locality of Francisco Javier Mina in Mexico, founded in 1882, preserves a particular identity orientation linked to its ancestors coming mainly from the Veneto Region, in Italy. From a theoretical approach of segmented assimilation, this article aims to show the development of decentralised international cooperation between the Chipileña community and the veneti town of Segusino, twinned with Chipilo, since 1982. Following a documentary collection methodology, with a qualitative interpretation approach of different testimonies, the results of the research reveal the importance of memory and transnational links in the processes of segmented assimilation for the descendants of immigrants in the societies that host them.